Climate Resilience In Agricultural Systems: How Do We Track Progress And Outcomes? - Bonilla Findji, Osana (2018)
B1: Climate Resilience In Agricultural Systems: How Do We Track Progress  And Outcomes? is by Osana Bonilla-Findji - science officer for CCAFS CSA Practices and Technologies Flagshp. Presented at the WBCSD Climate Smart Agriculture workshop at the University of Vermont, Burlington, VT on 27 March 2018.